2015
DOI: 10.1089/dna.2015.2904
|View full text |Cite
|
Sign up to set email alerts
|

miR-135a Targets and Regulates Prolactin Receptor Gene in Goat Mammary Epithelial Cells

Abstract: Mammary gland development and lactation are typical traits controlled by multiple genes, hormones, and regulatory factors. Prolactin receptor (PRLR), a specific receptor of prolactin, has been reported to have important physiological functions in regulating mammogenesis and lactogenesis. However, the post-transcriptional regulation mechanisms of PRLR expression have not yet been shown in detail. In this study, the expression of miR-135a and PRLR at different development stages of Laoshan dairy goat mammary gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For example, miR-135a expression level is associated with lactating stages and directly targets the prolactin receptor to function as a regulator in the goat mammary gland. 19 The expression level of miR-27a also was related to lactating stages and seems to play an important role in the regulation of TAG synthesis in GMEC. 31 There is evidence that miR-486 plays a key role in bovine mammary gland epithelial cells and promotes milk secretion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-135a expression level is associated with lactating stages and directly targets the prolactin receptor to function as a regulator in the goat mammary gland. 19 The expression level of miR-27a also was related to lactating stages and seems to play an important role in the regulation of TAG synthesis in GMEC. 31 There is evidence that miR-486 plays a key role in bovine mammary gland epithelial cells and promotes milk secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Sass et al (2015) found that the functional roles of miRNA could be finished via functional annotation of target genes and identification of mRNA/miRNA interactions [29]. Ji et al (2015) showed that prolactin receptor is a target gene of miR-135a that may play a key role in regulating the development and lactation of caprine mammary gland [30]. MiR-143 is a crucial post-transcription regulator that is related to caprine mammary cell survival, and it may have an effect on the development, lactation or involution of mammary gland [31].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of miRNAs in dairy lactation process or mammary gland development have been investigated using different approaches such as microarray3, RNA sequencing4567 and functional analyses of specific miRNAs891011121314. For instance, Wang et al 3.…”
mentioning
confidence: 99%